Overlapping neural circuits for visual attention and eye movements in the human cerebellum - Striemer, Christopher; Chouinard, Philippe; Goodale, Melvyn; de Ribaupierre, Sandrine (My University, 2015)
Previous research in patients with cerebellar damage suggests that the cerebellum plays a role in covert visual attention. One limitation of some of these studies is that they examined patients with heterogeneous cerebellar damage. As a result, the patterns of reported deficits have been inconsistent. In the current study, we used functional neuroimaging (fMRI) in healthy adults (N=14) to examine whether or not the cerebellum plays a role in covert visual attention. Participants performed two covert attention tasks in which they were cued exogenously (with peripheral flashes) or endogenously (using directional arrows) to attend to marked locations in the visual periphery without moving their eyes. We compared BOLD activation in these covert attention conditions to a number of control conditions including: the same attention tasks with eye movements, a target detection task with no cueing, and a self-paced button-press task. Subtracting these control conditions from the covert attention conditions allowed us to effectively remove the contribution of the cerebellum to motor output. In addition to the usual fronto-parietal networks commonly engaged by these attention tasks, lobule VI of the vermis in the cerebellum was also activated when participants performed the covert attention tasks with or without eye movements. Interestingly, this effect was larger for exogenous compared to endogenous cueing. These results, in concert with recent patient studies, provide independent yet converging evidence that the same cerebellar structures that are involved in eye movements are also involved in visuospatial attention.
Keywords: visual attention; covert attention; eye movements; cerebellum; fMRI